Historical consciousness and the use of the past in the ancient world - Baines, John 1946-; Blom, Henriette van der 1977-; Chen, Yi Samuel 1969-; Rood, Tim (equinox, 2019)
"This volume addresses crucial questions in current scholarship on historical consciousness and historiography. These questions include the formation of different traditions and the manifold uses of the past in particular socio-political contexts or circumstances; the ways in which these traditions and these types of cultural memory informed or contributed to the rise of more formal modes of historiography; interactions between formal modes of historiography and other traditions of historical consciousness during their transmission; and the implications of such interactions for cultural heritage, collective memory, and later understandings of history"...
Preface: "...The conference was held in Merton College, Oxford, on 17–19 September 2014..."
Keywords: Vor- und Frühgeschichte; History, Ancient -- Historiography; History, Ancient -- Methodology; Collective memory; Geschichtsbewusstsein; Geschichtsschreibung; Konferenzschrift